Asylum seeking children and adolescents in Australian immigration detention on Nauru: a longitudinal cohort study. Issue 1 (15th March 2020) - Zwi, Karen; Sealy, Louise; Samir, Nora; Hu, Nan; Rostami, Reza; Agrawal, Rishi; Cherian, Sarah; Coleman, Jacinta; Francis, Josh; Gunasekera, Hasantha; Isaacs, David; Larcombe, Penny; et al.
Abstract : Introduction: Immigration detention has a profound and negative impact on the physical health, mental health, development and social-emotional well-being of children, adolescents and their families. Australian clinicians will report results from detailed health and well-being assessments of asylum seeking children and adolescents who have experienced prolonged immigration detention. Methods and analysis: This is a national, multicentre study with a longitudinal cohort design that will document health and well-being outcomes of the children and adolescents who have been detained in offshore detention on the remote island of Nauru. Outcome measures will be reported from the time arrival in Australia and repeated over a 5-year follow-up period. Measures include demographics, residency history and refugee status, physical health and well-being outcomes (including mental health, development and social-emotional well-being), clinical service utilisation and psychosocial risk and protective factors for health and well-being (eg, adverse childhood experiences). Longitudinal follow-up will capture outcomes over a 5-year period after arrival in Australia. Analysis will be undertaken to explore baseline risk and protective factors, with regression analyses to assess their impact on health and well-being outcomes. To understand how children's outcomes change over time, multilevel regression analysis will be utilised. Structural equation modelling will be conducted to explore the correlation between baseline factors, mediational factors and outcomes to assess trajectories over time. Ethics and dissemination: This research project was approved by the Sydney Children's Hospitals Network Human Research Ethics Committee. Subsequent site-specific approvals have been approved in 5 of the 11 governing bodies where the clinical consultations took place. In order to ensure this research is relevant and sensitive to the needs of the cohort, our research team includes an asylum seeker who has spent time in Australian immigration detention. Results will be presented at conferences and published in peer-reviewed Medline-indexed journals.